TRAVEL VLOG DALAM MENCIPTAKAN DAN MEMPROMOSIKAN DESTINATION IMAGE - Pamuji, Dian Dhany; Yulianto, Edi; Kusumawati, Andriani (PROFIT: JURNAL ADMINISTRASI BISNIS, 2020)
Travel vlog which is one type of user-generated content (UGC) is becoming a marketing tool to promote a destination. Travel vlog have advantages, compared to text-based and image-based blog, then become a source of information for potential tourist before deciding to visit a destination. This article use literature review method, wants to answer the question, how effective the promotion of using travel vlogs is and the potential of vlog to create online destination image in social media. Travel vlogs have the potential to be used as a medium to create online destination image as projected online destionation image and to introduce it to the public through social media in order to become viral, then known as perceived online destination image. Promotion, whichÂ  popularly used to introduce destination image, it wil be very effective in influencing the millenial and iGen tourist if using vlog to promote, as they are the most users of social media nowadays. Buttravel vlogÂ  must be contains unique and interesting content to attract them.